Coups and framing: how do militaries justify the illegal seizure of power?. Issue 5 (3rd July 2020) - Yukawa, Taku; Hidaka, Kaoru; Kushima, Kaori
ABSTRACT: Since coups are essentially illegal acts that occur outside the bounds of political systems, militaries must justify their actions in some form after a successful coup. However, the methods militaries use to justify coups have not been systematically analysed. Therefore, this article focuses on framing as a method of obtaining legitimacy. An original dataset has been constructed that targets every successful coup that occurred between 1975 and 2014; this dataset is used to answer the question of how militaries have framed coups by examining the statements that militaries make after a coup. The results reveal two changes since the Cold War. The first is a change in label framing, in which the military asserts that an action is not a coup and the resultant regime is not a military government, thereby attempting to weaken the impression of the military's participation in the government itself. The second is a change in value framing in which militaries attempt to contend that their acts are democratic. The existence of these dynamics indicates that it is necessary to adapt to the normative environment of a given time, and the best method of doing so varies depending on the period.